The City of Progress - Edgren, Adolph Snow, Alvin Lincoln, 1862-1944
1909 The lyrics for "The City of Progress," a march dedicated to the Seattle Chamber of Commerce, were written by Alvin L. Snow, and the music was composed by prominent local musician and educator Adolph Edgren. The song was written for the Alaska-Yukon-Pacific Exposition (AYPE), a world's fair held in 1909 on the campus of Seattle's University of Washington to promote the development of the Pacific Northwest. The song was first performed by George F. Ward at a concert held during the fair on "Seattle Day," September 6, 1909. Professor Eric Adolph Edgren (1858-1921) emigrated from Sweden in 1892 and married Emma (Moeller) Edgren (1864-) in Nebraska seven years later. Together they operated the Edgren School of Music in Seattle, and later in Mount Vernon. Born in Illinois, Alvin L. Snow (1862-1944) married Ellen Belle Dorsey (1863-1949) in Iowa, and moved to Seattle about 1905. Apparently a man of many talents, Mr. Snow's occupation is listed in various U. S. Censuses as minister, real estate dealer, restaurant owner, policeman, and merchant. Caption information source: The Seattle Sunday Times, September 5, 1909, p. 5. Caption information source: "Alaska-Yukon-Pacific Exposition (1909): Music at the Fair" Peter Blecha, historylink.org Essay 8876. 1 score (6 p.) + 1 part 10.25 x 14 in.